Pengaruh Kualitas Pelayanan, Daya Tarik Wisata, dan Promosi terhadap Minat Kunjung Ulang Wisatawan pada Objek Wisata Pantai - Fadli Faturrahman (Yayasan Literasi Sains Indonesia, 2024)
The tourism phenomenon is seen as a complex process related to culture, lifestyle and a set of different demands for holidays and travel. As an activity, tourism has become an important part of the basic needs of developed communities and a small number of communities in developing countries. Tourism in Indonesia is an important economic sector. This research aims to analyze the influence of service quality, tourist attraction and promotion on tourist interest in repeat visits to beach tourism objects at the Saliper Ate beach tourist attraction, Sumbawa Regency. This research uses quantitative methods, with the types of data used, namely primary data and secondary data. The sample in the research was obtained using non-probability sampling techniques totaling 100 respondents. The data obtained was then processed using SPSS 16 software. The results of this study show that (1) the service quality variable has no significant effect on interest in repeat visits. (2) the tourist attraction variable has a significant and influential effect on interest in repeat visits. (3) promotional variables have a significant effect on interest in repeat visits.